The Effectiveness of Organizational Communication in Improving the Quality of Private Universities in Gorontalo - Jauhar Wahyuni; Imran Kamaruddin (Metafora: Education, Social Sciences and Humanities Journal, 2023)
This study aims to prove the existence of communication in organizations, especially in universities that have the effectiveness to change the attitudes and behavior of the academic community in an effort to improve the quality of higher education. Through a quantitative approach using path analysis and the results of questionnaire data processing on 182 respondents from two private universities in Gorontalo Province, namely Universitas Ichsan and Universitas Pohuwato. It can be concluded that communication in the organization has a significant effect on the quality of higher education. Aspects that contribute to organizational communication are aspects of relationships, pleasure, and action. Each aspect of organizational communication has different effects on both organizations. The differences that arise between the two universities are also shown by the differences in the dominant aspects in relation to improving the quality of private universities in Gorontalo.